Child mental health in primary health care: physicians’ speeches - Gomes, Fernanda Márcia de Azevedo; Cintra, Ana Maria de Oliveira; Ricas, Janete; Vecchia, Marcelo Dalla (Saúde e Sociedade, 2015)
The impacts of actions that ensure child's physical development, such as the reduction of the infant mortality rate and of the malnutrition taxes, have been significant on the last years. However, approximate 10 to 20% of the infant suffer with mental illnesses and, among them, 3 to 4% require intensive treatment. Considering this data, it is very important to understand how Primary Health Care (PHC) physicians deal with such issues. The research intended to understand the PHC physicians' meanings and significations related to Child Mental Health (CMH). Interviews were conducted with questions and a semi-structured script to build a sociodemographic characterization of the participants. It was possible to identify, as a result of the analysis process, five signification cores indicating that: (1) there are limitations related to the implication of conditions that involve CMH problems on the treatment, (2) “non-structured families” are considered determinant to the child's mental illness, (3) the mother is considered the main responsible for her son or daughter's mental health, (4) the medical prescription and the checking of follow-ups are central activities in CMH problems cases, and (5) the healthcare fragmentation due to the responsibilities segmentation on the CMH problems treatment. It is essential to develop an active listening to the needs of the families, mother and/or responsible adults that are related to the children that have mental health problems, as well as concentrating efforts to build intersectional actions and continuing education on CMH.